Wykonaj redukcję wyrazów podobnych:

a) 4xy + x + y – xy =

b) 5ab – 10b + 8ab – 3a =

c) x2 – 2xy – 0,5x2 – 3yx =

d) -1,5pq + 6p – 1,25p + 2qp =

e) 40m – 26mn + 7m – 32mn =

f) 3 x2y – 2x2 + 4,5yx2 – 1,6x2 =

g) 5,6n – 4,8mn – 0,8nm – 6,4n – 4m =

3

Odpowiedzi

2010-01-27T19:50:26+01:00
Jeśli masz np. x i -x to skreślasz -xy i xy , 2x i -2x rozumiesz to jest łatwe
1 2 1
Najlepsza Odpowiedź!
2010-01-27T19:53:28+01:00
A) 4xy + x + y – xy =x+y+3xy
b) 5ab – 10b + 8ab – 3a =13ab-3a-10b
c) x2 – 2xy – 0,5x2 – 3yx =0,5x2-5xy

d) -1,5pq + 6p – 1,25p + 2qp =0,5pq+4,75p
e) 40m – 26mn + 7m – 32mn =47m-58mn
f) 3 x2y – 2x2 + 4,5yx2 – 1,6x2 =-3,6x2+7,5x2y

g) 5,6n – 4,8mn – 0,8nm – 6,4n – 4m = -4m-5,6mn-0,8n
6 3 6
2010-01-27T19:54:01+01:00
A) 4xy + x + y – xy =x+y+3xy

b) 5ab – 10b + 8ab – 3a = -3a -10b +13ab

c) x2 – 2xy – 0,5x2 – 3yx = 0,5 x2 - 5xy

d) -1,5pq + 6p – 1,25p + 2qp = 4,75 p +0,5pq

e) 40m – 26mn + 7m – 32mn =47m -58mn

f) 3 x2y – 2x2 + 4,5yx2 – 1,6x2 = -3,6 x2 +7,5 x2y

g) 5,6n – 4,8mn – 0,8nm – 6,4n – 4m = -4m - 0,8n -5,6mn